European Building Construction Illustrated - Ching, Francis D. K (Wiley, 2014)
European Building Construction Illustrated provides a comprehensive and lucid presentation of everything from foundations and floor systems to finish work. Laying out the material and structural choices available, it provides a full understanding of how these choices affect a buildingâ€²s form and dimensions. Complete with more than 1000 illustrations, the book moves through each of the key stages of the design process, from site selection to building components, mechanical systems and finishes.; Includes bibliographical references and index; KR302 Cấu tạo kiến trúc 01; KR069 Chuyên đề kiến trúc 03: Trang thiết bị công trình